Who Are Our Students? Understanding Students' Personality for Refined and Targeted Physical Education. A Scoping Review - Kirch, Alina; Schnitzius, Melina; Mess, Filip; Spengler, Sarah (Frontiers in Sports and Active Living, 2019)
Students’ personality is an essential component in order to plan and teach physical education (PE) lessons according to students’ individual needs. Additionally, personality formation in general is part of the educational mandate and student personality development specifically is considered as an elementary goal of PE. Although student personality is a central topic in the PE context, the state of research, especially regarding the underlying personality understandings, is diverse and hard to capture. Therefore this scoping review aims to I) describe the underlying personality understandings and II) analyze research questions and results of studies examining students’ personality in PE. We conducted a scoping review. Eleven databases were chosen because of their specification within the field of education, sports and health sciences. We included references if they empirically examined students’ personality in PE and were published in German or English. Twenty-four studies were included in the review. Fifteen of the included studies were cross-sectional, nine longitudinal. Regarding aim I), the underlying personality understandings were inconsistent across the studies but most of the studies followed trait theory. Considering aim II), the included studies investigated relationships between students’ personality and either a) students’ achievement in PE, b) students’ psychological determinants of PE participation (e.g. motivation, anxiety) or c) a school sports intervention. Results indicated that e.g. extraverted students tend to enjoy PE more and obtain less anxiety in PE. The review showed that students’ personality in PE is empirically examined but the studies’ underlying personality understandings, research questions and results are diverse. Findings highlight that PE contributes to students’ personality development. Additionally, the review showed that results of personality research in PE context can be used in order to teach PE in a student-centered way (e.g. by deducing the detected relationships considering extraversion) and by this support students’ lifelong physical activity. Further and targeted research in this field can help PE teachers to tailor their teaching to their students’ needs. This increases the chances to achieve PE’s two main goals – ‘educating to sports (e.g. personality-aligned lessons addressing different motives)’ and ‘educating through sports (e.g. personality development)’ in the long term.